Brill's companion to the reception of Socrates - Moore, Christopher, 1981- (Brill's Companions to Classical Reception, 2019)
Brill's Companion to the Reception of Socrates , edited by Christopher Moore, provides almost unbroken coverage, across three-dozen studies, of 2450 years of philosophical and literary engagement with Socrates - the singular Athenian intellectual, paradigm of moral discipline, and inspiration for millennia of philosophical, rhetorical, and dramatic composition. Following an Introduction reflecting on the essentially "receptive" nature of Socrates' influence (by contrast to Plato's), chapters address the uptake of Socrates by authors in the Classical, Hellenistic, Roman, Late Antique (including Latin Christian, Syriac, and Arabic), Medieval (including Byzantine), Renaissance, Early Modern, Late Modern, and Twentieth-Century periods. Together they reveal the continuity of Socrates' idiosyncratic, polyvalent, and deep imprint on the history of Western thought, and witness the value of further research in the reception of Socrates.